COVID-19 Battle in Rural India: Current Status and Future Prospects (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
As the pandemic’s second wave makes further inroads into India’s hinterland, the country might be watching the likelihood of a disaster almost like what occurred within the urban regions early this year. And since 65.53 percent of the country’s entire population is rural, targeted, comprehensive strategies must be undertaken to stop such a catastrophe from happening. Things are already dire, and require immediate attention: medical infrastructures are weak, there are severe shortages in qualified medical staff, the vaccine rollout is slow, and there's poor adherence to safety protocols. These, including enduring, large-scale poverty and lack of livelihoods—which have existed long before COVID-19.This special report outlined a ten point agenda for immediate action in India’s rural districts. Beyond this urgent course of action, however, it's equally important that India turns the crisis into a chance to rethink current approaches to development: instead of being urban-centric, India must develop better health and welfare systems within the rural regions and make the countryside more resilient to shocks like COVID-19. The blueprint presented during this report can go an extended way in not only addressing the present health crisis in India’s villages, but also within the achievement of cross-cutting sustainable development goals: SDG 1 (no poverty); 2 (zero hunger); 3 (good health and well-being); 5 (gender equality); 8 (decent work and economic growth); and 10 (reduced inequalities).